Synthesis, Characterization and Photocatalysis of Mesoporous TiO2 - Zhang, Xiangchao; Jia, Yanrong; Yu, Qumin; Tang, Aidong; Zhang, Shiying (Asian Journal of Chemistry, 2014)
The mesoporous TiO2 nanoparticulate has been prepared by evaporation induced self-assembly method using EO-PO type polyether P123 as a template. The small angle X-ray diffraction, wide angle X-ray diffraction, high-resolution transmission electron microscopy and N2 isothermal adsorption-desorption are used to study the microstructure and morphology of the as-synthesized mesoporous TiO2. The results demonstrate that the mesoporous TiO2 belongs to anatase and the size is 20-30 nm. The sample is prepared using P123 as a template with average pore size distribution of 11.54 nm, specific surface area of 84.83 m2/g and pore volume of 0.234 cm3/g. The as-synthesized mesoporous TiO2 exhibits remarkably high photocatalytic activity of 93.6 % in decomposing formaldehyde under ultraviolet light irradiations for 90 min. This work provides a basic experimental process for the preparation of mesoporous TiO2, which will possess a broad prospect in terms of the applications in improving indoor air quality.